Health‐related quality of life and treatment strategies in myasthenia gravis. Issue 4 (5th October 2020) - Utsugisawa, Kimiaki; Nagane, Yuriko; Uzawa, Akiyuki; Murai, Hiroyuki; Imai, Tomihiro; Suzuki, Shigeaki
Abstract: Our multicenter studies have repeatedly shown that disease severity and oral steroid dose are major independent factors negatively impacting health‐related quality of life (QOL) in patients with myasthenia gravis (MG). Even if pharmacological remission is achieved, QOL is low in patients taking oral prednisolone >10 mg/day. Disease severity tends to affect QOL by decreasing personal activities, whereas insufficiently reduced steroids affects QOL by decreasing social activities. MG patients often experience unemployment and decreased income, and many patients report reduced social positivity. More effort is required to reduce both the severity and dose of oral steroids. QOL in patients with minimal manifestations (MM) or better status who are treated with prednisolone at ≤5 mg/day (MM‐or‐better‐5 mg) is almost identical to that in patients achieving complete stable remission. Early achievement of MM‐or‐better‐5 mg is now recommended as a target for MG treatment in Japan. However, our studies suggested that the percentage of patients achieving MM‐or‐better‐5 mg was not high in 2010 and 2012 (<40% of generalized MG patients), and was not considered to be increased by physician skill in steroid dosing. In Japan, treatment strategies are now being reconsidered to further increase treatment success, placing a focus on helping MG patients resume a normal lifestyle by achieving the target as soon as possible. An initial attempt to achieve early MM‐or‐better‐5 mg for some period through aggressive use of non‐oral fast‐acting therapies can be more important for patient QOL, even if long‐term stability cannot be provided. Abstract : In Japan, treatment strategies are now being reconsidered to further increase treatment success, placing a focus on helping myasthenia gravis patients resume a normal lifestyle by achieving the target as soon as possible. An initial attempt to achieve early minimal manifestations or better status when treated with prednisolone at ≤5 mg/day for some period through aggressive use of non‐oral fast‐acting therapies can be more important for patient quality of life, even if long‐term stability cannot be provided.